DISEMINASI TEKNOLOGI, MANAJEMEN PRODUKSI DAN STRATEGI PEMASARAN UKM PENGOLAHAN ROTI DAN PIZZA DI KABUPATEN PANGKAJENE KEPULAUAN - Jassin, Ernawati; Muhtar, Imran; Ahmad, Ilham; Saleh, Rahmawati; Laylah, Nur; Hatulesila, Jan Willem (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
Low technological and management capacity has a direct impact on the low capacity and performance of MSMEs, thus requiring empowerment strategies to improve the competence of these MSMEs. This community empowerment aims to improve the competence of Noura Pizza and Bakery (NPB) MSME human resources through dissemination and training in technology, production management, and digital marketing for icreasing the MSME competence. The empowerment results have increased competency in using processing equipment and implementing occupational health and safety (OHS) from 35% to 85%, the ability to carry out production processes in accordance with GMP and sanitation and hygiene has increased from 45% to 90%, and digital marketing competency has increased from 45% to 87%. Overall, SME competency achievement exceeded 80%, with an average increase of 45.6%. This indicates that the dissemination and training have improved the competency of operating production equipment, OSH, production management, and digital marketing for SMEs. This condition provides a prediction of a significant positive impact from empowerment activities in achieving the independence and competitiveness of SMEs through assistance from universities.